Examining the Effects of School Composition on North Carolina Student Achievement over Time - Southworth, Stephanie (Education Policy Analysis Archives, 2010)
This study explores the effects of school-level characteristics on North Carolina students’ reading and math achievement from fourth through eighth grade, focusing on the relationships between achievement and the racial and poverty composition of schools. After creating race-by-poverty cohorts of schools, I use multilevel models to examine math and reading achievement for the same students in fourth, sixth, and eighth grades. The racial and poverty composition of schools affect student achievement after factoring in student, family, and other school influences. In addition, increasing teacher quality and school resources reduces but does not eliminate the effects of school racial and poverty composition on student achievement. Policies leading to reductions in racial and poverty isolation in schools and increases in teacher quality should be pursued to guarantee equality of educational opportunities to all children in North Carolina schools.